Autophagy buffers Ras-induced genotoxic stress enabling malignant transformation in keratinocytes primed by human papillomavirus - Cararo-Lopes, Eduardo; Dias, Matheus H.; da Silva, Marcelo S.; Zeidler, Julianna D.; Vessoni, Alexandre T.; Reis, Marcelo S.; Boccardo, Enrique; Armelin, Hugo A. (Springer Nature, 2021)
Malignant transformation involves an orchestrated rearrangement of cell cycle regulation mechanisms that must balance autonomic mitogenic impulses and deleterious oncogenic stress. Human papillomavirus (HPV) infection is highly prevalent in populations around the globe, whereas the incidence of cervical cancer is 0.15%. Since HPV infection primes cervical keratinocytes to undergo malignant transformation, we can assume that the balance between transforming mitogenic signals and oncogenic stress is rarely attained. We showed that highly transforming mitogenic signals triggered by HRasG12V activity in E6E7–HPV–keratinocytes generate strong replication and oxidative stresses. These stresses are counteracted by autophagy induction that buffers the rapid increase of ROS that is the main cause of genotoxic stress promoted by the oncoprotein. As a result, autophagy creates a narrow window of opportunity for malignant keratinocytes to emerge. This work shows that autophagy is crucial to allow the transition of E6E7 keratinocytes from an immortalized to a malignant state caused by HRasG12V.